The effectiveness of standardized advertising for Cartier in Chinese market - Tian, Lingyun (2017)
There had been much Debate on standardized advertising and specialized adverting for a few decades and more and more advertisers are suggesting the use of standardized advertising approach for companies (Ryans and Donnelly, 1969). In the early time, it was called for a standardized advertising by Fatt (1967) to use the advertising with similar campaign or theme in the international market. later, there were Levitt (1983), Harris (1994), Duncan and Ramaprasad (1995), Zou and Cavusgil (2002) proposed the application of standardization of advertising for the positive result of the financial and strategic results.